Oscillatory Flow and Heat Transfer Within Parallel-plate Heat Exchangers of Thermoacoustic Systems - Mohd Saat, Fatimah Al Zahrah; Jaworski, Artur (2013)
Oscillatory flows past solid bodies are a feature typical for thermoacoustic systems. Understanding such flows is one of the keys for improving the system performance. This work investigates oscillatory flows around parallel-plate heat exchanger through numerical modeling developed based on the experimental data obtained in-house within a standing-wave thermoacoustic setup. Attention is given to developing a model that can explain the physics of phenomena observed in the experimental work. Four drive ratios (defined as maximum pressure amplitude to mean pressure) were investigated: 0.3%, 0.45%, 0.65% and 0.83%. The suitability of selected turbulence models for predicting the flow phenomena at varied drive ratios has been tested. Discussion of results is based on the velocity profiles and vorticity contours within the flow. Associated heat transfer phenomena are also discussed.